Integrasi Teknologi Blockchain Dalam Pengelolaan Wakaf: Mewujudkan Transparansi dan Akuntabilitas untuk Keberlanjutan Lembaga Pendidikan Islam - K.H. Sofwan Manaf; Uswatun Khasanah; Sabiila Khoirin Ni'mah (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2026)
This study analyses the role of blockchain in strengthening transparency and accountability in waqf management within Islamic educational institutions and its implications for institutional sustainability. Weak transparency and accountability have long eroded public trust and constrained the sustainability of waqf-dependent institutions. Employing a qualitative Systematic Literature Review guided by the PRISMA protocol, the study screened literature indexed in Scopus, Web of Science, and SINTA published between 2015 and 2025, from which ten studies met the inclusion criteria and were analysed thematically. The findings show that blockchain advances transparency through real-time tracking, reinforces nazhir accountability through immutable audit trails, and cultivates public trust that drives donor participation. Blockchain thus functions not merely as a technical innovation but as a governance infrastructure, although its success depends on institutional readiness rather than technological sophistication alone.